2019
DOI: 10.3390/s19245409
|View full text |Cite
|
Sign up to set email alerts
|

A Graphene-Based Glycan Biosensor for Electrochemical Label-Free Detection of a Tumor-Associated Antibody

Abstract: The study describes development of a glycan biosensor for detection of a tumor-associated antibody. The glycan biosensor is built on an electrochemically activated/oxidized graphene screen-printed electrode (GSPE). Oxygen functionalities were subsequently applied for covalent immobilization of human serum albumin (HSA) as a natural nanoscaffold for covalent immobilization of Thomsen-nouvelle (Tn) antigen (GalNAc-O-Ser/Thr) to be fully available for affinity interaction with its analyte—a tumor-associated antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Heavy metals have been analyzed by electrochemical biosensor from water in the work of Sciuto and coauthors (2020), copper from water samples was determined in the work of Cui and coauthors (2014), and iron from the water was tested in the work of Kamal and coauthors (2014) [83][84][85]. Glycan electrochemical biosensor for cancer diagnosis was presented in the work of Kveton and coauthors (2019), the electrochemical behavior of phosphotyrosine was observed in the work of Popa and Duculescu (2013), and dual-mode sensor using an electrolyte-insulator-semiconductor fieldeffect device coupled with nanoplasmonic effects was developed for protein phosphorylation detection in the work of Bhalla and coauthors (2015) [86][87][88]. So, various electrochemical biosensors exist, but their optimization and application in AD diagnosis were not tried yet.…”
Section: Perspectives In the Diagnosis Of Alzheimer's Diseasementioning
confidence: 99%
“…Heavy metals have been analyzed by electrochemical biosensor from water in the work of Sciuto and coauthors (2020), copper from water samples was determined in the work of Cui and coauthors (2014), and iron from the water was tested in the work of Kamal and coauthors (2014) [83][84][85]. Glycan electrochemical biosensor for cancer diagnosis was presented in the work of Kveton and coauthors (2019), the electrochemical behavior of phosphotyrosine was observed in the work of Popa and Duculescu (2013), and dual-mode sensor using an electrolyte-insulator-semiconductor fieldeffect device coupled with nanoplasmonic effects was developed for protein phosphorylation detection in the work of Bhalla and coauthors (2015) [86][87][88]. So, various electrochemical biosensors exist, but their optimization and application in AD diagnosis were not tried yet.…”
Section: Perspectives In the Diagnosis Of Alzheimer's Diseasementioning
confidence: 99%
“…The addition of nanomaterials such as nanoparticles, carbon nanotubes or graphene-based materials may enhance the sensitivity of biosensors. In particular, "Graphene-Based Glycan Biosensor for Electrochemical Label-Free Detection of a Tumor-Associated Antibody" [4] describes the development of a glycan biosensor for the detection of a tumor-associated antibody. This glycan ultrasensitive biosensor is built on an electrochemically activated/oxidized graphene screen-printed electrode.…”
Section: Contributionsmentioning
confidence: 99%
“…In our work, we developed a label-free electrochemical approach for the detection of an antibody against an aberrant form of a glycan—Tn antigen [ 121 ]. In this case, the Tn antigen was covalently attached to a pre-immobilized layer of BSA on the surface of an electrochemically activated screen-printed graphene electrode.…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%
“…The electrochemical oxidation of the graphene interface had two distinct roles: a) to form –COOH groups applied to covalent immobilization of BSA via amine coupling; and b) to render the surface more hydrophilic and thus more accessible for the aqueous assay buffer and proteins examined (antibody and lectin). The study showed that the lectin could be detected down to 1 aM, while the antibody against the Tn antigen down to 10 aM [ 121 ]. The main aim of the study was to develop an ultrasensitive biosensor device for the detection of antibodies against aberrant glycans, which can be effective used as biomarkers in the diagnosis of several types of cancers [ 122 ].…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%